Isolation and evolutionary analysis of feline panleukopenia virus strains FPV-BJ-J2 and FPV-BJ-J3 (T440A, N564S, A568G) in Beijing, China - Su, Xia; Zhou, Hongzhuan; Jiang, Wenqian; Xu, Fuzhou; Xiao, Bing; Zhang, Jin; Qi, Qi; Yang, Bing (Frontiers in Veterinary Science, 2026)
Feline panleukopenia virus (FPV) is a single-stranded linear DNA virus with high lethality, whose VP2 protein determines viral host range and antigenicity. Substitutions at several key VP2 residues are closely associated with enhanced virulence and immune evasion. However, their patterns and temporal evolutionary dynamics remain poorly characterized. In this study, we analyzed global FPV VP2 gene sequences that were retrieved from the NCBI database and seven FPV VP2 sequences newly isolated by our laboratory during 2024–2025. Multiple sequence alignment was performed using MAFFT, and phylogenetic trees were constructed with IQ-TREE. Meanwhile, mutation characteristics were further analyzed using Shannon entropy. The results revealed that VP2 hypervariable regions were mainly concentrated in nt 111–411, nt 477–1,038, and nt 1,500–1752, with the highest entropy peak at nt 271 (aa 91), which corresponds to the A91S substitution. Temporal dynamics analysis revealed that the frequency of the A91S substitution has markedly increased since 2017, suggesting ongoing positive selection. The high-frequency I101T substitution has stabilized, suggesting an adaptive equilibrium. Conversely, the substitution frequency at residue 232 has gradually declined over time. Notably, this study for the first time identified a T440A substitution in the newly isolated FPV-BJ-J2 and FPV-BJ-J3 strains. This 440A site, which is located on the viral capsid surface, co-occurs with N564S and A568G, exhibiting the characteristic substitution combination of CPV-2c, which may be associated with enhanced immune evasion of FPV. Overall, this study systematically reveals the temporal evolutionary characteristics of key VP2 residues, providing important theoretical insights for FPV molecular epidemiology and vaccine strain optimization.